The Relationship between Smoking Severity, Tumor Stage and Histological Differentiation Of Bladder Tumors Between Smokers and Non-Smokers At The First Diagnosis of The Tumor - مرهج يزن; محمد كنعان; أيمن حرفوش (Latakia University Journal -Medical Sciences Series, 2022)
* Aim of the study: The aim of this study is to study The Relationship Between Smoking Severity, Tumor Stage, and Histological Differentiation Of Bladder Tumors Between Smokers and Non-Smokers At The First Diagnosis Of The Tumor. * Patients and methods: The study was Observational prospective study. Study time and place: Tishreen University Hospital in the period between 10/4/2021 and 10/4/2022. * Results: All patients diagnosed with TCC in the first diagnosis of the tumor of the bladder with different tumor stages and degrees of histological differentiation were selected in the Urology Department of Tishreen University Hospital. And was disqualified: 1-Patients with metastatic bladder tumors (rectum – uterus …) and their number (8). 2-Patients who underwent previous curettage or recurrent bladder tumors patients and their number (20). 3-Patients with non-Tcc bladder tumors (it has other risk factors besides smoking) and their number (2). 4-Patients with incomplete information and their number (5). Thus, the final case sample in the study reached (77) patients. The sample included (77) patients (61 male 79.22%) and (16 female 20.78%) distribute as follows: Non-smoker 0 (0%) Smoker under 10 years 20 patients (32.47%) Smoker from 10 to 20 years 25 patients (25.97%) Smoker for more than 20 years 32 patients (41.56%) All study patients were smokers therefore the first subgroup (smoker under 10 years) was adopted as a comparison group. After collecting the data, distributing the results and applying the statistical program, the following is noted: 1-The ages of the patients in the study sample ranged from 40-84 years and were the ages of the males 40-84 years and female ages 48-72 years. The largest age group in the study sample was between (60-69 years) in the rate of 49.35% (38 patients). This indicates an increased risk of developing a bladder tumor with age, especially in those over 60 years old. However, according to the results, there is no relationship to age with an increase in the stage of the tumor (T) or an increase in the degree of histological differentiation (G) of the tumor. 2-The incidence of males: females (4:1) that is, there is an important statistical difference in the prevalence of bladder cancer tumors between males and females. 3-Smokers of 10-20 years have a 3.95 times greater risk of developing a High Grade tumor compared to smokers of less than 10 years P value=0.03 , while for smokers for more than 20 years, this risk increases to 4.75 times compared to smokers for less than 10 years P value=0.01, thus the study suggests that the degree of Histological differentiation (G) increases with the increase in smoking time. 4-Smokers of 10-20 years have a 4.33 times greater risk of developing invasive muscular bladder tumor (MIBC) than smokers of less than 10 years P value=0.03, on the other hand, smokers of more than 20 years have a 5.58 times greater risk of developing invasive muscular bladder tumors than smokers of less than 10 years P value=0.008 , therefore, the study suggests that the stage (T) of the bladder tumor increases with the increase in smoking time. *conclusion: Smoking is an important risk factor for TCC type bladder tumor, and the stage of the tumor (T) and the degree of histological differentiation of the tumor increase with the duration of smoking.